2016
DOI: 10.1534/g3.116.033340
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Genes Cause Postmating Prezygotic Reproductive Isolation in theDrosophila virilisGroup

Abstract: Understanding the genetic basis of speciation is a central problem in evolutionary biology. Studies of reproductive isolation have provided several insights into the genetic causes of speciation, especially in taxa that lend themselves to detailed genetic scrutiny. Reproductive barriers have usually been divided into those that occur before zygote formation (prezygotic) and after (postzygotic), with the latter receiving a great deal of attention over several decades. Reproductive barriers that occur after mati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…virilis females is somewhat complex: at least three regions on the centromeric half of chromosome 5 (Muller C) and a large inversion on chromosome 2 (Muller E) carry genes responsible for the paternal component of PMPZ [2,49].…”
Section: /28mentioning
confidence: 99%
See 3 more Smart Citations
“…virilis females is somewhat complex: at least three regions on the centromeric half of chromosome 5 (Muller C) and a large inversion on chromosome 2 (Muller E) carry genes responsible for the paternal component of PMPZ [2,49].…”
Section: /28mentioning
confidence: 99%
“…A striking pattern of PMPZ in this group is the strong incompatiblity between D. americana males and females from the sister species. Quantitative trait loci (QTL) that contribute to this paternal incompatibility between D. americana and D. virilis females have been mapped in two studies [2,49], and include a large inversion on chromosome 2 and several adjacent QTL on the centromeric half of chromosome 5. We found that the four SFPs with the highest ω values reside within the chromosome 2 inversion (Figure 7).…”
Section: Molecular Evolution Of Male Reproductive Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…For internal fertilizers, an additional array of potential PMPZ reproductive barriers can act as a result of the complex series of events that take place within the female reproductive tract after mating (Bloch Qazi, Heifetz, & Wolfner, 2003;Orr & Brennan, 2015;Schnakenberg, Siegal, & Bloch Qazi, 2012). In single heterospecific matings, successful fertilization can be decreased or prevented by reduced sperm transfer by males, and/or reduced transport, storage, and viability of hetero-specific sperm in females (Ahmed-Braimah, 2016;Kelleher & Markow, 2007;Kohyama, Matsubayashi, & Katakura, 2016;Larson, Hume, Andrés, & Harrison, 2012;Manier et al, 2013;Reinhardt, 2006;Rose, Brand, & Wilkinson, 2014). PMPZ isolation has also been suggested to occur when hetero-specific matings result in reduced egg production compared to con-specific matings, even though fertilization is successful (e.g., Matute & Coyne, 2010;Turissini, McGirr, Patel, David, & Matute, 2018).…”
mentioning
confidence: 99%